2020
DOI: 10.2147/ccid.s275512
|View full text |Cite
|
Sign up to set email alerts
|

<p>Contraception, Sexuality and Pregnancy in Women with Psoriasis: Real-Life Experience of 235 Women</p>

Abstract: Background Little is known about how women of childbearing age with psoriasis experience contraception, sexuality and pregnancies through the lens of their skin condition. Objective To evaluate the experiences and expectations in this group of patients. Materials and Methods In total, 235 women aged between 18 and 45 years old completed an online survey. We collected the characteristics of psoriasis, contraception and pregnancy history. Psori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…In the current study, 7.3% of women reported being afraid of becoming pregnant because of their eczema. This figure is similar to a recent study whereby 8% of women with psoriasis were concerned that psoriasis influenced their pregnancy plans ( 27 ). However, unlike in psoriasis, pregnancy worsens AD in 17–61% of patients, and up to 73% in women with premenstrual syndrome ( 26 , 28 , 29 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, 7.3% of women reported being afraid of becoming pregnant because of their eczema. This figure is similar to a recent study whereby 8% of women with psoriasis were concerned that psoriasis influenced their pregnancy plans ( 27 ). However, unlike in psoriasis, pregnancy worsens AD in 17–61% of patients, and up to 73% in women with premenstrual syndrome ( 26 , 28 , 29 ).…”
Section: Discussionsupporting
confidence: 91%
“…Improvements in shared decision-making between patients and HCPs could facilitate more integrated treatment pathways for women with psoriatic disease, potentially addressing the high proportion of women in this survey who reported a low or moderate level of general support from HCPs. These results may indicate a lack of open communication between patients and HCPs, supporting the results of previous studies in psoriatic disease ( Gottlieb et al, 2019 ; Maccari et al, 2019 ; 2020 ). Improved training for HCPs focusing on facilitating discussions with patients about their treatment preferences and concerns could help alleviate some negative outcomes reported in this survey.…”
Section: Discussionsupporting
confidence: 89%
“…A high proportion of women also reported disease flares during and after pregnancy, indicating potential worsening of their condition at this time. Many women reported a low or moderate level of support from HCPs while pregnant or attempting to conceive, supporting studies in other long-term inflammatory conditions that suggested an unmet need for patient information and a low awareness of relevant treatment guidelines among HCPs treating pregnant patients ( Ackerman et al, 2015 ; Andreoli et al, 2019 ; Maccari et al, 2019 ; 2020 ; Nelson-Piercy et al, 2019 ). Commonly used guidelines, such as the 2012 European Alliance of Associations for Rheumatology guidelines for PsA treatment, often do not contain specific advice on treatment during pregnancy, and although the European Alliance of Associations for Rheumatology has separately published points to consider for the use of antirheumatic drugs before and during pregnancy, comparable guidelines for the treatment of pregnant women with dermatological diseases are lacking ( Gossec et al, 2012 ; Götestam Skorpen et al, 2016 ; Gottlieb et al, 2019 ).…”
Section: Discussionmentioning
confidence: 63%
“…Seven studies answer this question [27,28,[33][34][35][36][37]. The evolution of psoriasis during pregnancy is unpredictable and worsening is observed in all studies (Table 3).…”
Section: How Does Psoriasis Behave During Pregnancy?mentioning
confidence: 96%
“…Eight articles answer this question [22,[26][27][28][29][30][31][32]. There seems to be an increased risk of complications during pregnancy.…”
Section: Does Psoriasis Affect the Course Of Pregnancy?mentioning
confidence: 99%